Barisan Nasional in GE 14: miscalculating the political campaign - Syed Abdullah Idid, Syed Arabi (2018)
This paper analyses the loss of Barisan Nasional (BN), a dominant party that had ruled Malaysia for the last 60 years and the rise of a new party Pakatan Harapan (PH), during the recent General Elections. The objective is to understand the campaigns launched during the 14th General Election, the strategies and the issues championed. The question is posed whether campaigns matter? Can campaigns affect election outcome by influencing voter attitude and behaviour? This paper used findings from several studies to evaluate the effectiveness of campaigns by illustrating how campaigns used communication to acclaim, attack and defend their positions to gain voter sympathy (Benoit, 2007). There were advantages in the acclaim, attack and defense for BN but they were of no might to the attacks launched by PH against BN. BN’s strategy was premised of a return to power with a stronger majority causing party officials to conduct a campaign strategy geared more for party members than the voters. On the other hand, Pakatan Harapan assumed themselves as underdogs to woo the voters. Several issues influenced negatively the BN campaigns. Declaring Wednesday a voting day in the hope to have a low voter turnout and thus work to its advantage, disfavoured BN when voters expressed sympathy with the opposition parties. The redelineation exercise where several constituencies were amended, did not work to the advantage of BN as they were assumed to be. BN had assumed the popularity of their past programmes and policies with the voters as contained in the manifestos. Our studies found voters to generally favour issues highlighted by PH than BN.